Exploring the influence of students’ Matric Accounting knowledge on the successful completion of a BCom Accounting mainstream degree: A comparative study at a university in the Western Cape - Williams, B.; dos Reis, K.; Yu, D. (South African Journal of Higher Education, 2022)
Studies conducted nationally found that students with Matric Accounting knowledge performed significantly better than students without it in university-level Accounting modules (Baard, Steenkamp, and Kidd 2010; Papageorgiou 2017; Steenkamp, Baard, and Frick 2009). However, the reality at South African universities is that Accounting as a school subject is not always a requirement to pursue BCom Accounting studies. This situation means that at certain universities, Accounting as a school subject is not taken into consideration for this degree, while this is the case at some universities. This study focuses on two cohorts of students enrolled for the mainstream programme in 2017‒2019 at a South African university. The reason for focusing on these two cohorts was to establish the throughput rate of students with or without Matric Accounting knowledge. Two most significant findings of this study are that firstly, students who obtained at least 70 per cent for Matric Accounting completed the degree within the minimum three-year time frame, while students who obtained at least 80 per cent had a higher throughput rate of 48.8 per cent. Secondly, students who achieved lower than 70 per cent for Mathematics and did not complete Matric Accounting were unable to complete the degree in the minimum timeframe. The research methodology includes both quantitative and qualitative methods. The results can inform the selection and admission criteria at tertiary institutions and inform other stakeholders in higher education on how school subjects and grades influence students’ throughput rate.